Sovereignty and extortion: a new state form in Mexico : the 2021 lectures at El Colegio Nacional - Lomnitz-Adler, Claudio (Public planet books, 2024)
"Over the past fifteen years in Mexico, over 450,000 people have been murdered and 110,000 more have been disappeared. In Sovereignty and Extortion, Claudio Lomnitz examines the Mexican State in relation to this extreme violence, uncovering a reality that challenges the familiar narratives of "a war on drugs" or a "failed state." Tracing how neoliberal reforms, free trade agreements, and a burgeoning drug economy have shaped Mexico's socio-political landscape, Lomnitz shows that the current crisis does not represent a tear in the social fabric. Rather, it reveals a fundamental shift in the relationship between the state and the economy in which traditional systems of policing, governance, and the rule of law have eroded. Lomnitz finds that power is now concentrated in the presidency and enforced through militarization, which has left the state estranged from itself and incapable of administering justice or regaining control over violence. Through this critical examination, Lomnitz offers a new theory of the state, its forms of sovereignty, and its shifting relation to capital and militarization"--